Prion Protein Does Not Confer Resistance to Hippocampus-Derived Zpl Cells against the Toxic Effects of Cu2+, Mn2+, Zn2+ and Co2+ Not Supporting a General Protective Role for PrP in Transition Metal Induced Toxicity. - Pradeep Kumar Reddy Cingaram; Antal Nyeste; Divya Teja Dondapati; Elfrieda Fodor; Ervin Welker (PLoS ONE, 2015)
The interactions of transition metals with the prion protein (PrP) are well-documented and characterized, however, there is no consensus on their role in either the physiology of PrP or PrP-related neurodegenerative disorders. PrP has been reported to protect cells from the toxic stimuli of metals. By employing a cell viability assay, we examined the effects of various concentrations of Cu2+, Zn2+, Mn2+, and Co2+ on Zpl (Prnp-/-) and ZW (Prnp+/+) hippocampus-derived mouse neuronal cells. Prnp-/- Zpl cells were more sensitive to all four metals than PrP-expressing Zw cells. However, when we introduced PrP or only the empty vector into Zpl cells, we could not discern any protective effect associated with the presence of PrP. This observation was further corroborated when assessing the toxic effect of metals by propidium-iodide staining and fluorescence activated cell sorting analysis. Thus, our results on this mouse cell culture model do not seem to support a strong protective role for PrP against transition metal toxicity and also emphasize the necessity of extreme care when comparing cells derived from PrP knock-out and wild type mice.